2023
DOI: 10.1371/journal.pone.0290045
|View full text |Cite
|
Sign up to set email alerts
|

Monkeypox genome mutation analysis using a timeseries model based on long short-term memory

Refat Khan Pathan,
Mohammad Amaz Uddin,
Ananda Mohan Paul
et al.

Abstract: Monkeypox is a double-stranded DNA virus with an envelope and is a member of the Poxviridae family’s Orthopoxvirus genus. This virus can transmit from human to human through direct contact with respiratory secretions, infected animals and humans, or contaminated objects and causing mutations in the human body. In May 2022, several monkeypox affected cases were found in many countries. Because of its transmitting characteristics, on July 23, 2022, a nationwide public health emergency was proclaimed by WHO due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…The results indicated that CNNs performed the best in modeling the virus's spread, while time-series analysis using ARIMA and SARIMA models provided valuable insights for risk assessment and preventive measures. Pathan et al [134] used a deep learning-based LSTM model to analyze the gene mutation rate of the MPox virus. The work of Eid et al [135] introduced a novel approach called BER-LSTM, which optimized LSTM deep networks using the Al-Biruni Earth Radius (BER) algorithm to predict MPox cases accurately.…”
Section: Review Of Work Related To Time-series Forecasting In the Con...mentioning
confidence: 99%
“…The results indicated that CNNs performed the best in modeling the virus's spread, while time-series analysis using ARIMA and SARIMA models provided valuable insights for risk assessment and preventive measures. Pathan et al [134] used a deep learning-based LSTM model to analyze the gene mutation rate of the MPox virus. The work of Eid et al [135] introduced a novel approach called BER-LSTM, which optimized LSTM deep networks using the Al-Biruni Earth Radius (BER) algorithm to predict MPox cases accurately.…”
Section: Review Of Work Related To Time-series Forecasting In the Con...mentioning
confidence: 99%